Pembelajaran Tari Zapin Lancang Kuning Menggunakan Metode Drill di Sekolah Menengah Atas Negeri 1 Ujan Mas - Egretha Try Tianti Pasaribu; Nofroza Yelli; Muhsin Ilhaq (Mahesa Research Center, 2022)
The purpose of this study was to identify and describe the learning process of the Zapin Lancang Kuning dance using the drill method in class X SMA Negeri 1 Ujan Mas. This research method is a qualitative descriptive with data collection techniques of observation, interviews, and documentation. In collecting data, the researcher observed directly the learning process in the classroom both regarding teachers and students starting from the preparation, implementation and evaluation stages of learning. This research was conducted at SMA Negeri 1 Ujan Mas in class X IPA 3 with a total of 36 students consisting of 13 boys and 23 girls. The method used by the teacher is the drill method, in which the teacher in terms of learning is first provided with theory by the teacher plus also showing dance videos as a medium in learning so that students are interested and respond to learning. The teacher demonstrates the dance moves in front of the students and then remains guided by the teacher, students are asked to practice with repeated exercises so that they become proficient and skilled. The results of this study indicate that the implementation of the Zapin Lancang Kuning dance learning in Class X SMA Negeri 1 Ujan Mas is categorized as good, judging from the results of the evaluation of students who get scores in the good category range of 24 people and very good category 12 people.